THE EFFECT OF TEAM GAME TOURNAMENT ON MOTIVATION TO LEARN AND SCIENCE LEARNING OUTCOMES ELEMENTARY SCHOOL - Harry Bandaso; Abdullah Sinring; Priska Efriani Luansi Ero (Jurnal Tunas Bangsa, 2023)
Ilmu Pengetahuan Alam (IPA) adalah salah satu pembelajaran yang penting di Sekolah Dasar (SD). oleh karena itu, perlu meningkatkan motivasi dan hasil belajar siswa dalam prosesnya. Salah satu faktor yang mempengaruhi motivasi dan hasil belajar adalah model pembelajaran. Riset ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran kooperatif Team Games Tournament (TGT) dengan motivasi belajar dan hasil belajar IPA siswa. Melalui pendekatan kuantitatif dan dengan desain penelitian eksperimen model one group pretest posttest, data dianalisis menggunakan analisis statistik inferensial dengan uji t data motivasi dan hasil belajar IPA. Data diperoleh dari sampel yang merupakan siswa kelas V SDN 131 Balombong Kabupaten Tana Toraja. Berdasarkan deskripsi dan analisis data menunjukan bahwa terjadi peningkatan motivasi dan hasil belajar IPA siswa setelah diberikan pembelajaran dengan model kooperatif tipe Team Games Tournament (TGT). Selain itu berdasarkan analisis dengan uji t diperoleh nilai signifikan 0.00<0.05 untuk motivasi dan hasil belajar IPA yang menunjukan bahwa terdapat pengaruh yang signifikan dari penggunaan pembelajaran kooperatif tipe Team Games Tournament (TGT) terhadap motivasi dan hasil belajar IPA siswa kelas V SDN 131 Balombong. A B S T R A C TScience is one of the important learning in Elementary School (SD). therefore, it is necessary to increase student motivation and learning outcomes in the process. One of the factors that influence motivation and learning outcomes is the learning model. This research aims to determine the effect of applying the Team Games Tournament (TGT) cooperative learning model with students' learning motivation and science learning outcomes. Through a quantitative approach and with an experimental research design with one group pretest posttest, the data were analyzed using inferential statistical analysis with t test of motivation data and science learning outcomes. Data were obtained from samples of fifth grade students of SDN 131 Balombong, Tana Toraja Regency. Based on the description and analysis of the data, it shows that there is an increase in students' motivation and science learning outcomes after being given learning with the Team Games Tournament (TGT) type cooperative model. In addition, based on the analysis with the t test, a significant value of 0.00 <0.05 was obtained for the motivation and learning outcomes of science which shows that there is a significant effect of the use of cooperative learning type Team Games Tournament (TGT) on the motivation and learning outcomes of science of grade V students of SDN 131 Balombong.